The synergistic effect of GNPs plus CNTs on properties of polyester: comparison with polyester-CNTs nanocomposite - Guler, Omer; Basgoz, Oykum; Guler, Seval Hale; Canbay, Canan A.; Acikgoz, Sehzat; Boyrazli, Mustafa (Springer, 2021)
Numerous studies have revealed the properties of composites obtained by adding carbon nanotubes (CNTs) into different polymer matrices. Although CNTs significantly improve the properties of the polymer matrix, problems are experienced in the production of composites due to CNTs. Therefore, only graphene nanoplates (GNPs) at the same rate along with CNTs were added into the polyester matrix which was used as a matrix in this study. In this way, the changes occurring in the properties of polyester were revealed. The mechanical properties of CNTs-GNPs reinforced polyester composite are lower than the composites reinforced only with CNTs. Besides, electrical conductivity of CNTs reinforced polyester composite was lower than CNT + GNP reinforced composite. Mechanical properties and electrical conductivity of both polyester-CNTs composite and polyester-CNT + GNP composite increased with increasing reinforcement ratio. In addition, the thermal properties were examined and glass transition temperature was determined as averagely 79 degrees C.
Keywords: Carbon Nanotubes; Percolation-Threshold; Mechanical-Properties; Graphene; Dispersion; Hybrid; Resin; Conductivity; Composites